Pengaruh Platform Digital Terhadap Pola Konsumsi Di Kalangan Milenial - Fitrah Rianti; Risda; Miyana; Suraidah (Jurnal Ekonomi dan Bisnis Digital, 2025)
Digital platforms have become an integral part of millennials' lives, influencing various aspects of their lives, including consumption patterns. This study aims to analyze the impact of digital platform usage on millennials' consumption patterns in Indonesia. This study uses a quantitative approach by directly interviewing information sources (people), observation, and documentation. The results of the study show that digital platforms influence millennials' consumption behavior in terms of product choices, purchase frequency, and payment preferences. In addition, social media and e-commerce applications have proven to be the main catalysts for changes in consumption patterns. This study provides important implications for business actors to understand millennial consumer behavior in the digital era.